Harvest Strategies for an Ecosystem Approach to Fisheries Management in Western Mediterranean Demersal Fisheries - Quetglas, Antoni; Merino, Gorka; González, Javier; Ordines, Francesc; Garau, Antoni; Grau, Antoni M.; Guijarro, Beatriz; Oliver, Pere; Massutí, Enric (Frontiers in Marine Science, 2017)
The serious overfishing of most Mediterranean stocks demands urgent reforms of the management measures aiming to guarantee the sustainability of resources, notably when compared with the improvement observed in other European areas. The new EU Common Fisheries Policy (CFP) constitutes an excellent opportunity to introduce the changes needed for such a reform. According to this CFP, all European fish stocks should be brought to a state where they can produce at MSY by 2020 at the latest. The CFP also establishes that the objective of sustainable exploitation should be achieved through multiannual plans (MAPs) adopted in consultation with relevant stakeholders having fisheries management interests such as fishermen, non-governmental organizations, and policy makers. Together with the MSY and MAP approaches, the new CFP contains several other measures, directed to guarantee the ecological and socio-economic sustainability of fisheries by means of the implementation of the ecosystem approach to fisheries management (EAFM). With this new perspective, the CFP wants to avoid past failures of fisheries management based on monospecific approaches. This study is a first step toward the application of the EAFM in the Balearic Islands by means of the development of a harvest strategy with defined objectives, targets, limits, and clear management control rules aimed at optimizing socioeconomic and ecological objectives in the framework of the new CFP. Different management scenarios designed to achieve that goal were modeled for the main demersal commercial fisheries from the study area, the bottom trawl, and small-scale fisheries. The work begins with a general description of those fisheries, their main fishing grounds, and assessments of the exploitation status of the main target stocks in order to establish the current situation. Secondly, alternative management scenarios to maximize catch and profits while considering societal objectives were evaluated by means of bio-economic models. Thirdly, management measures were provided based on the previous modeling and discussions with stakeholders. Finally, a monitoring scheme was outlined to assess the progresses of the proposed management actions. This work is intended to be a working example of co-management (fishers, policy-makers, and scientists) in the Mediterranean in the framework of the new EU CFP.